Anatomy‐based, patient‐specific VMAT QA using EPID or MLC log files. (8th May 2015) - Defoor, Dewayne L.; Vazquez‐Quino, Luis A.; Mavroidis, Panayiotis; Papanikolaou, Nikos; Stathakis, Sotirios
Abstract : In this project, we investigated the use of an electronic portal imaging device (EPID), together with the treatment planning system (TPS) and MLC log files, to determine the delivered doses to the patient and evaluate the agreement between the treatment plan and the delivered dose distribution. The QA analysis results are presented for 15 VMAT patients using the EPID measurements, the ScandiDos Delta 4 dosimeter, and the beam fluence calculated from the multileaf collimator (MLC) log file. EPID fluence images were acquired in continuous acquisition mode for each of the patients and they were processed through an in‐house MATLAB program to create an opening density matrix (ODM), which was used as the input fluence for the dose calculation in the TPS (Pinnacle 3 ). The EPID used in this study was the aSi1000 Varian on a Novalis TX linac equipped with high‐definition MLC. The actual MLC positions and gantry angles were retrieved from the MLC log files and the data were used to calculate the delivered dose distributions in Pinnacle. The resulting dose distributions were then compared against the corresponding planned dose distributions using the 3D gamma index with 3 mm / 3 % passing criteria. The ScandiDos Delta 4 phantom was also used to measure a 2D dose distribution for all the 15 patients and a 2D gamma was calculated for each patient using the Delta 4 software. The average 3D gamma using the EPID images was 96.1 % ± 2.2 % . The average 3D gamma using the log files was 98.7 % ± 0.5 % . The average 2D gamma from the Delta 4 was 98.1 % ± 2.1 % . Our results indicate that the use of the EPID, combined with MLC log files and a TPS, is a viable method for QA of VMAT plans. PACS numbers: 87.55.Qr